Sobre operadores entre espaços de sequências que atingem a norma - Silva, Juan Carlo da Cruz (2009)
In this work we present a recent result, due to D. Pellegrino and E. V. Teixeira, that characterizes the continuous linear operators between lpspaces which attain their norms. To this end, we Örstly explore some topics from the Banach space theory, such as Banachís Theorem for basis, Bessaga-Pe ̃czynski Selection Principle and Pittís Theorem.